Cryotherapy and balloon dilatation for subglottic stenosis in a neonate: a case report - Siswanto, Johanes Edy; Akira Prayudijanto; Muhammad I. Prayudijanto; David D. Putra; Istifa Amalia; Rifan Fauzie; Christophorus AS Pamungkas (Indonesian Journal of Biomedicine and Clinical Sciences, 2025)
Cryotherapy and balloon dilatation are combined treatments for subglottic stenosis (SGS) in newborns. Cryotherapy involves freezing the affected area with extremely low temperatures, which can result in tissue destruction. Balloon dilatation is a technique in which a balloon is inflated in the narrow subglottic area to widen the airway. We reported a case of SGS in a neonate who was treated with a combination of cryotherapy and balloon dilatation to contribute to the growing body of evidence of the therapy and provide information for clinicians in the care of the vulnerable patients. A 22-day-old female baby, who weighed 2,600 gr at birth, was transferred to our hospital from another facility. We conducted cryotherapy on the granulation tissue area until it was released, then inflated the balloon for 5 cycles (30 sec each) with a pressure of 5-6 atm. After cryotherapy and balloon dilatation, the patient was examined using direct laryngoscopy, which revealed subglottic stenosis up to 9.5 cm from the outer border of the mouth. To maintain airway patency for the next 24 hr, the patient was intubated with an endotracheal tube number 3.5. The patient's condition improved after this intervention, and they no longer required oxygen therapy support. The patient was discharged without the need for supported oxygen. In conclusion, to manage the challenges associated with post-intubation subglottic stenosis (PI-SGS), a comprehensive approach that includes a reliable referral system, thorough bronchoscopy training, and a multi-disciplinary team is essential.